2015
DOI: 10.1093/jamia/ocv144
|View full text |Cite
|
Sign up to set email alerts
|

Alert dwell time: introduction of a measure to evaluate interruptive clinical decision support alerts

Abstract: Metrics for evaluating interruptive prescribing alerts have many limitations. Additional methods are needed to identify opportunities to improve alerting systems and prevent alert fatigue. In this study, the authors determined whether alert dwell time-the time elapsed from when an interruptive alert is generated to when it is dismissed-could be calculated by using historical alert data from log files. Drug-drug interaction (DDI) alerts from 3 years of electronic health record data were queried. Alert dwell tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…These additional limits to the alert were an attempt to limit unnecessary alerts as part of our ongoing efforts to understand the risks for alert fatigue in our setting and make corresponding refinements. 55,56 The implementation of pharmacogenomic data into the EHR with CDS must also be considered in the broader context of an organization’s overall approach to clinical genomics and the EHR, and the core requirements for genomics in the EHR that are being further defined. 42,43 …”
Section: Future Directionsmentioning
confidence: 99%
“…These additional limits to the alert were an attempt to limit unnecessary alerts as part of our ongoing efforts to understand the risks for alert fatigue in our setting and make corresponding refinements. 55,56 The implementation of pharmacogenomic data into the EHR with CDS must also be considered in the broader context of an organization’s overall approach to clinical genomics and the EHR, and the core requirements for genomics in the EHR that are being further defined. 42,43 …”
Section: Future Directionsmentioning
confidence: 99%
“…We also considered implementation and human factors‐related issues important for clinical decision support development. Since alert fatigue is a main concern, careful consideration was given when integrating the new TBI decision rules into the current system that already employs reminders to alert providers of other tasks . We used expert opinion of clinicians to prioritize tasks and develop clinical decision support that is relevant for anesthesia providers.…”
Section: Discussionmentioning
confidence: 99%
“…Since alert fatigue is a main concern, careful consideration was given when integrating the new TBI decision rules into the current system that already employs reminders to alert providers of other tasks. [18][19][20] We used expert opinion of clinicians to prioritize tasks and develop clinical decision support that is relevant for anesthesia providers. Indeed, this study makes apparent the challenges of influencing physician behavior during emergent, nonroutine cases.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers have shown that inappropriate design of CDSS DOI: 10.1159/000489503 alerts could lead to CDSS inefficiency. In fact, the problem of alert fatigue, in addition to creating user dissatisfaction, is that it causes users to ignore serious alerts and endangers patient safety [89,90]. Hence, many articles [89,91] focused on CDSS-related studies in other areas on assessing the quality of alerts provided in the CDSS and evaluating the effectiveness of these alerts.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the problem of alert fatigue, in addition to creating user dissatisfaction, is that it causes users to ignore serious alerts and endangers patient safety [89,90]. Hence, many articles [89,91] focused on CDSS-related studies in other areas on assessing the quality of alerts provided in the CDSS and evaluating the effectiveness of these alerts. Effectiveness assessment of alerts designed in chemotherapy prescription CDSS is highly significant for continuous improvement of these systems and user satisfaction enhancement.…”
Section: Discussionmentioning
confidence: 99%